Fonio (Digitaria exilis (Kippist) Stapf): A Socially Embedded Cereal for Food and Nutrition Security in Senegal - Diop, Baye Magatte; Gueye, Mame Codou; Agbangba, Codjo Emile; Cisse, Ndiaga; Deu, Monique; Diack, Omar; Fofana, Amadou; Kane, Ndjido Ardo; Ndir, Khadidiatou Ndoye; Ndoye, Ibrahima; Ngom, Ablaye; Leclerc, Christian; et al. (Ethnobiology Letters, 2018)
Agricultural diversification with neglected and underutilized species is a viable way to sustainably increase the productivity of agrosystems. Understanding the social, cultural, and ecological roles of these species is crucial for their promotion. White fonio (Digitaria exilis), a neglected cereal endemic to West African Sahelian countries, is recognized as a crop for the future due to its cultural, nutritional, and economic values. In this study, we described fonio farming systems in Senegal through an ethnobotanical approach. As expected in family farming systems, farmers largely practiced diversified subsistence agriculture on small plots and relied on local seed exchange networks. The importance of fonio varied among agroecological zones, ethnic groups, and gender. In the Groundnut Basin, where agriculture is more mechanized, late-maturing landraces of fonio are cultivated as a cash crop rather than a staple crop. However, in southern Senegal, where food shortages are recurrent, fonio is more widespread and the cultivation of both early- and late-maturing landraces contributes to local food security. These differences also reflect the cultural status of fonio: different among ethnic groups and more important for women than for men. Finally, the regressive dynamics of fonio cultivation in most regions emphasizes the need to develop integrated conservation and promotion strategies that take into account the diversity of social and agronomical roles of the plant.